EFFECTS OF PHISICAL EXERCISE IN TREATMENT OF JUVENILE IDIOPATHIC ARTHRITIS: A SISTEMATIC REVIEW - da Silveira, Josiane Santos; Moura, Vágner Winck; Toigo, Adriana Marques (Journal of Health Care, 2017)
Introduction: The Juvenile Idiopathic Arthritis (JIA) is an autoimmune disease, chronic, of unknown etiology, that affects children under 16 years of age, characterized by joint pain and swelling that may progress to impairment of cartilage and bone, resulting in loss of function and joint deformities. Physical exercises are supposed to improve physical performance, so it can be suggested as adjunctive therapy to conventional treatment of JIA. However, the question is what would be the most appropriate exercise for these individuals. Objective: To look for evidence in the scientific literature about the potential benefits of the practice of physical exercise by people with JIA. Method: A search in PubMed and SciELO databases, using the terms rheumatoid arthritis, juvenile rheumatoid arthritis, juvenile idiopathic arthritis, physical activity, physical exercise, physical training, gymnastics, running and sport was held. Results: Seven papers were selected for analysis of the results, as they fulfilled the inclusion criteria. As there were few studies on the effects of exercise in JIA and the authors have used different tests and training protocols, it was difficult to establish some comparisons. Conclusion: Although all the factors that contribute to the occurrence of rheumatoid arthritis (RA) are widely studied, mainly genetic and immunological factors, the precise mechanisms involved in the initiation, progression and autoimmune destruction present in JIA are not fully elucidated. Evidence specified suggests that exercise can and should be encouraged and added to the drug treatment to benefit people with JIA, in order to reduce clinical symptoms related to the disease. There were no adverse effects related to exercise, confirming this as adjunctive therapy to the treatment of JIA.